Tetrasomy 15Q11-Q13 identified by fluorescence in situ hybridization in a patient with autistic disorder - Silva, Ana Elizabete [UNESP] (2002)
We report a female child with tetrasomy of the 15q11-q13 chromosomal region, and autistic disorder associated with mental retardation, developmental problems and behavioral disorders. Combining classical and molecular cytogenetic approaches by fluorescence in situ hybridization technique, the karyotype was demonstrated as 47,XX,+mar.ish der(15)(D15Z1++,D15S11++,GABRB3++,PML-). Duplication of the 15q proximal segment represents the most consistent chromosomal abnormality reported in association with autism. The contribution of the GABA receptor subunit genes, and other genes mapped to this region, to the clinical symptoms of the disease is discussed.